2021
DOI: 10.1038/s41418-021-00762-7
|View full text |Cite
|
Sign up to set email alerts
|

The noncoding RNAs SNORD50A and SNORD50B-mediated TRIM21-GMPS interaction promotes the growth of p53 wild-type breast cancers by degrading p53

Abstract: Small nucleolar RNA SNORD50A and SNORD50B (SNORD50A/B) has been reported to be recurrently deleted and function as a putative tumor suppressor in different types of cancer by binding to and suppressing the activity of the KRAS oncoproteins. Its deletion correlates with poorer patient survival. However, in this study, we surprisingly found that SNORD50A/B loss predicted a better survival in breast cancer patients carrying wild-type p53. Functional studies showed that SNORD50A/B deletion strongly inhibited the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…SNORA6, SNORA31, SNORA62, SNORA71C, SNORD37, and SNORD50B were significantly downregulated in CLL compared to normal total tonsillar B-cells. Downregulation of SNORD50B has also been observed in a variety of other human cancers, including breast cancer [ 90 ], lung cancer [ 91 ], melanoma [ 91 ] and T-cell lymphoma [ 91 ]. The expression of SNORA31 in CLL patients correlated with the expression of its host gene, tumor protein translationally controlled 1 (TPT1), which is an important target of TP53 [ 92 ].…”
Section: Dysregulation Of Snornas In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…SNORA6, SNORA31, SNORA62, SNORA71C, SNORD37, and SNORD50B were significantly downregulated in CLL compared to normal total tonsillar B-cells. Downregulation of SNORD50B has also been observed in a variety of other human cancers, including breast cancer [ 90 ], lung cancer [ 91 ], melanoma [ 91 ] and T-cell lymphoma [ 91 ]. The expression of SNORA31 in CLL patients correlated with the expression of its host gene, tumor protein translationally controlled 1 (TPT1), which is an important target of TP53 [ 92 ].…”
Section: Dysregulation Of Snornas In Cllmentioning
confidence: 99%
“…SNORD50A and SNORD50B both directly bind and inhibit K-RAS . Deletion of these snoRNAs leads to an increased activity of oncogenic K-RAS signaling, suggesting a functional role for loss of these snoRNAs in CLL development [ 90 , 91 ]. In addition, the snoRNA host gene 5 (SNHG5), which harbors SNORD50A/B, is confirmed to regulate chemotherapy resistance by modulating the SNHG5/miR-32/DNAJB9 axis in AML patients [ 93 ].…”
Section: Dysregulation Of Snornas In Cllmentioning
confidence: 99%
“…More recently, it was reported that SNORD50A and SNORD50B also enhance the interaction between the ubiquitin ligase TRIM21 and its substrate GMPS subsequently influencing the interaction of GMPS with p53. Depending on p53 mutational status this interaction would either promote or inhibit malignant phenotype of breast cancer cells [ 128 ]. Another example is SNORD12B, a snoRNA predicted to target 28S-G3899(3878) [ 129 ].…”
Section: Extra-ribosomal Functions Of Box C/d Snornasmentioning
confidence: 99%
“…Very interestingly, many other interactions with functional outcomes have been identified in the last years. The SNORD50A-SNORD50B locus produces snoRNAs that interact with the FIP1 subunit of the cleavage and polyadenylation specificity factor (CPSF) to modulate mRNA 3 -end processing [221], with the proto-oncogene KRAS to inhibit its activity [222,223] or with the E3 ubiquitin ligase TRIM21 and its substrate Guanosine 5 -monophosphate synthase (GMPS) to increase their interaction [224]. Numerous C/D and H/ACA snoRNAs have been proposed to interact with the poly-ADPribosyltransferase PARP1 independently of DNA damage and to stimulate its catalytic activity in the nucleolus, leading to ADP-ribosylation of the RNA helicase DDX21 and increased rDNA transcription [225].…”
Section: The Diversity Of C/d Snorna Molecular Partners and Targetsmentioning
confidence: 99%